Patients with faecal peritonitis admitted to European intensive care units: An epidemiological survey of the GenOSept cohort - Tridente, A; Clarke, G; Walden, A; McKechnie, S; Hutton, P; Mills, G; Gordon, A; Holloway, P; Chiche, J; Bion, J; Stuber, F; Garrard, C; et al. (2014)
Introduction: Faecal peritonitis (FP) is a common cause of sepsis and admission to the intensive care unit (ICU). The Genetics of Sepsis and Septic Shock in Europe (GenOSept) project is investigating the influence of genetic variation on the host response and outcomes in a large cohort of patients with sepsis admitted to ICUs across Europe. Here we report an epidemiological survey of the subset of patients with FP. Objectives: To define the clinical characteristics, outcomes and risk factors for mortality in patients with FP admitted to ICUs across Europe. Methods: Data was extracted from electronic case report forms. Phenotypic data was recorded using a detailed, quality-assured clinical database. The primary outcome measure was 6-month mortality. Patients were followed for 6 months. Kaplan-Meier analysis was used to determine mortality rates. Cox proportional hazards regression analysis was employed to identify independent risk factors for mortality. Results: Data for 977 FP patients admitted to 102 centres across 16 countries between 29 September 2005 and 5 January 2011 was extracted. The median age was 69.2 years (IQR 58.3-77.1), with a male preponderance (54.3 %). The most common causes of FP were perforated diverticular disease (32.1 %) and surgical anastomotic breakdown (31.1 %). The ICU mortality rate at 28 days was 19.1 %, increasing to 31.6 % at 6 months. The cause of FP, pre-existing co-morbidities and time from estimated onset of symptoms to surgery did not impact on survival. The strongest independent risk factors associated with an increased rate of death at 6 months included age, higher APACHE II score, acute renal and cardiovascular dysfunction within 1 week of admission to ICU, hypothermia, lower haematocrit and bradycardia on day 1 of ICU stay. Conclusions: In this large cohort of patients admitted to European ICUs with FP the 6 month mortality was 31.6 %. The most consistent predictors of mortality across all time points were increased age, development of acute renal dysfunction during the first week of admission, lower haematocrit and hypothermia on day 1 of ICU admission. © 2013 Springer-Verlag Berlin Heidelberg and ESICM.